PERBANDINGAN PENAMBAHAN BETA KAROTEN ATAU GLISEROL DALAM PENGENCER TRIS KUNING TELUR TEHADAP KUALITAS SEMEN BEKU KERBAU LUMPUR (Bubalus bubalis): COMPARISON OF THE ADDITION OF BETA CAROTENE OR GLYCEROL IN EGG YOLK TRIS DILUENT ON FROZEN SEMEN QUALITY MUD BUFFALO (Bubalus bubalis) - Putri Juni; Rini Elisia; Maiyontoni Maiyontoni; Refika Komala (Tropical Animal Science, 2026)
The objective of this study was to determine the quality of frozen buffalo semen after adding Beta-carotene or glycerol to the tris egg yolk diluent on the quality of frozen buffalo semen. The study used 14 straws of frozen semen from mud buffaloes originating from BIB Tuah Sakato, Ibuh Payakumbuh. The experimental research method with data analysis used a completely randomized design with 7 treatments and 2 replicates: P0 without the addition of Beta-carotene or glycerol, treatment with the addition of Beta-carotene to egg yolk tris (TKT) at concentrations: P1 0.1%, P2. 0.2%, P3 0.3%, and Glycerol at concentrations: P4 2%, P5 4%, and P6 6%. The equipment and materials used included: a microscope, computer-assisted semen analysis (CASA), object glass, cover glass, 14 straws of frozen buffalo semen, citrate, egg yolk, HOS solution, and eosin-nigrosin dye. The parameters observed after the thawing process were the percentages of motility, viability, MPU, and abnormalities in frozen semen. The results of the study showed the average sperm motility in order, namely P1 57.79 ± 5.30, P4 57.71 ± 9.01, P0 54.62 ± 8.92, P5 51.47 ± 5.80, P2 49.28 ± 7.59, P3 25.45 ± 1.21, and P6 25.03 ± 1.21. Treatments P3 and P6 significantly (P < 0.05) reduced sperm motility after thawing. Meanwhile, viability, MPU, and abnormality did not show significant differences (P > 0.05) between treatments. From these data, it can be concluded that the addition of Beta-carotene at concentrations of 0.1%, 0.2%, and 0.3% compared to the addition of glycerol at 2%, 4%, 6% in the egg yolk tris diluent, both significantly (P < 0.05) affected motility and did not significantly (P > 0.05) affect viability, intact plasma membrane, and abnormalities in frozen buffalo semen. The addition of Beta-carotene up to 0.2% or glycerol up to 4% was able to maintain post-thawing motility (PTM) above 40%.